Highly efficient induction of primate iPS cells by combining RNA transfection and chemical compounds. (17th June 2019) - Watanabe, Toshiaki; Yamazaki, Shun; Yoneda, Nao; Shinohara, Haruka; Tomioka, Ikuo; Higuchi, Yuichiro; Yagoto, Mika; Ema, Masatsugu; Suemizu, Hiroshi; Kawai, Kenji; Sasaki, Erika
Abstract: Induced pluripotent stem (iPS) cells hold great promise for regenerative medicine and the treatment of various diseases. Before proceeding to clinical trials, it is important to test the efficacy and safety of iPS cell‐based treatments using experimental animals. The common marmoset is a new world monkey widely used in biomedical studies. However, efficient methods that could generate iPS cells from a variety of cells have not been established. Here, we report that marmoset cells are efficiently reprogrammed into iPS cells by combining RNA transfection and chemical compounds. Using this novel combination, we generate transgene integration‐free marmoset iPS cells from a variety of cells that are difficult to reprogram using conventional RNA transfection method. Furthermore, we show this is similarly effective for human and cynomolgus monkey iPS cell generation. Thus, the addition of chemical compounds during RNA transfection greatly facilitates reprogramming and efficient generation of completely integration‐free safe iPS cells in primates, particularly from difficult‐to‐reprogram cells. Abstract : This study reports a novel method for iPS cell generation by combining RNA transfection and chemical compounds. Our novel method enable highly efficient induction of iPS cells in marmosets, it can be used in other primates as well.